THE KINETICS OF AUSTENITE TRANSFORMATION IN THE RAIL STEEL GRADES M74 AND 75XHSM DURING CONTINUOUS COOLING - Tkachenko, F. K.; Kuzmin, S. O.; Yefremenko, V. H.; Kazankov, V. H. (Science and Transport Progress, 2009)
The particularities of the shaping of microstructure of rail steels of marks М74 and 75ХГСМ under continuous cooling with different velocities from austenite interval of temperature are described; the temperature borders of the areas of phase transformations are presented.